the KARAKTERISASI MORFOLOGI DAN BIOKIMIA ISOLAT PGPR DARI RUMPUT GAJAH (Pennisetum purpureum): KARAKTERISASI MORFOLOGI DAN BIOKIMIA ISOLAT PGPR DARI RUMPUT GAJAH (Pennisetum purpureum) - Rahmat Lamadi; Maria Massora; Rina A. Mogea; Hermawaty Abubakar; Rinondon Altje R Mogea (Jurnal Natural, 2026)
Intensive and prolonged use of inorganic fertilizers in Indonesia remains predominant among farmers; however, it can lead to soil contamination and reduced fertility over time. Biofertilizers provide a sustainable alternative, with Plant Growth-Promoting Rhizobacteria (PGPR) serving as key components naturally associated with plant roots. This study aimed to isolate and characterize PGPR from the roots of elephant grass (Pennisetum purpureum) collected from Amban Pantai Manokwari- West Papua. Isolation procedures involved preparing PGPR starters, purifying colonies, and conducting macroscopic and microscopic observations along with biochemical tests. Macroscopic analysis revealed six isolates with white colonies; shapes were circular (PGPR 1 and 5) or irregular (others); elevations included convex, raised, flat, and umbonate; margins were undulate or rhizoid; and oxygen requirements ranged from aerobic, obligate aerobic, anaerobic, to facultative anaerobic. Microscopically, all isolates were rod-shaped and motile, with Gram-positive (PGPR 2 and 3) or Gram-variable (PGPR 1, 4, 5, and 6) characteristics. Biochemical assays indicated positive sucrose fermentation (all isolates, though partial in some), lactose and dextrose fermentation (mainly PGPR 1 and 3), gelatin hydrolysis (PGPR 1, 3, and 5), citrate utilization (PGPR 5), MR positivity (all isolates), VP positivity (PGPR 2 and 4), H₂S production (only PGPR 4), negative indole, and absence of gas production. These findings demonstrate significant morphological and metabolic diversity among the isolated PGPR, underscoring their potential as biofertilizer candidates for sustainable agriculture in tropical regions such as West Papua. The characterization analysis revealed that the isolates belong to the genera Bacillus (PGPR 1, 2, 3, 5, 6) and Enterobacter (PGPR 4).